Land Concentration, Institutional Control and African agency: Growth and Stagnation of European Tobacco Farming in Shire Highlands, c 1900 – 1940 - Erik Green (African Economic History Network (AEHN), 2012)
The role of factor endowments and institutions as drivers of socio-economic change and development is a central theme in economic and agrarian history. The common approach is to identify either factor endowments or institutions as triggers of change. Meanwhile, institutions and factor endowments are interdependent and the puzzle is to identify the causality within the structure of interdependence. This paper is an attempt to relate factor endowments with institutions from a specific theoretical angle, following Griffin et al proposed hypothesis of the connections between land concentration and labour control. The paper discusses to what extent land concentration in the southern province of colonial Malawi during the early colonial period created specific institutions of labour control that determined agricultural growth on European controlled tobacco farms. The paper concludes that the European farmers' control of labour was severely restricted due to African farmers' (tenants as well as peasants) engagement in cash crop production. The labour contracts were therefore to a large extent designed to meet the demands of the Africans. Land concentration had little impact on European farmers' capacity to control labour. On the contrary, African agency played a significant role in shaping the institutional framework in which the European farmers operated in.
Keywords: N17; N57; 330; Institutions; settler; Malawi; labour; labour control